Heterologous Expression of Recombinant L-asparaginase Genes - Pokrovskaya, M.V.; Alexandrova, S.S.; Pokrovsky, V.S.; Dobryakova, N.D.; Shishparenok, A.N.; Gladilina, Yu.V.; Zhdanov, D.D. (Biomedical Chemistry: Research and Methods, 2025)
L-asparaginase (EC 3.5.1.1.) is the enzyme with the highest level of global production and is used in the treatment of cancer and in the food industry. Different expression systems are used for the production of many target proteins, ranging from cell-free to hyperproductive plant, insect, bacterial and mammalian cells. This review attempts to bring together the available literature data on heterologous gene expression and technology for the production of recombinant L-asparaginases.